2014
DOI: 10.1016/j.jpeds.2014.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gray Matter Volume and School Age Anxiety in Children Born Late Preterm

Abstract: Objectives To determine if late preterm (LP) children differ from full term (FT) children in volumes of the cortex, hippocampus, corpus callosum, or amygdala and whether these differences are associated with anxiety symptoms at school-age. Study design LP children born between 34 and 36 weeks gestation and FT children born between 39 and 41 weeks gestation from a larger longitudinal cohort had MRI scans at school-age. Brain volumes, cortical surface area and thickness measures were obtained. Anxiety symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 57 publications
5
26
2
3
Order By: Relevance
“…Most notably, increased connectivity was found between the left superficial amygdala and the STS in this group but not in controls. Structural alterations in the STS have been previously reported in VPT samples (Nosarti et al 2008; Rogers et al 2014). This region – and in particular its posterior portion (Hein & Knight, 2008)- is well known as a face-sensitive region specialized for dynamic feature recognition (Haxby et al 2000; Andrews & Ewbank, 2004; Engell & Haxby, 2007), including eye and mouth movements (Puce et al 1998; Hoffman & Haxby, 2000) and emotional expressions (LaBar et al 2003).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Most notably, increased connectivity was found between the left superficial amygdala and the STS in this group but not in controls. Structural alterations in the STS have been previously reported in VPT samples (Nosarti et al 2008; Rogers et al 2014). This region – and in particular its posterior portion (Hein & Knight, 2008)- is well known as a face-sensitive region specialized for dynamic feature recognition (Haxby et al 2000; Andrews & Ewbank, 2004; Engell & Haxby, 2007), including eye and mouth movements (Puce et al 1998; Hoffman & Haxby, 2000) and emotional expressions (LaBar et al 2003).…”
Section: Discussionmentioning
confidence: 62%
“…Volumetric alterations have been shown in VPT samples in brain regions thought to subserve emotion processing, such as the amygdala (Peterson et al 2000), orbitofrontal cortex (GimĂ©nez et al 2006), fusiform gyrus (Nosarti et al 2008; Gousias et al 2012), hippocampus (Rogers et al 2012; Omizzolo et al 2013; Aanes et al 2015) and insula (Nosarti et al 2014). Moreover, both structural magnetic resonance imaging (MRI) and diffusion MRI studies, have found significant associations between brain alterations in regions typically implicated in socio-emotion processing and specific social and emotional outcomes in VPT samples (Rogers et al 2012, 2014; Healy et al 2013; Fischi-GĂłmez et al 2015). However, to our knowledge, no neuroimaging study to date has investigated resting-state functional connectivity (rs-fc) in emotion-processing networks and performance on emotional processing tasks in individuals born VPT.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with infants born full term, the late preterm brain manifests neurodevelopmental immaturity, characterized by lower brain volume and less differentiated patterns of myelination and neural connectivity. 34 -37 These structural differences in the brains of children born late preterm, including lower gray matter volume present in infancy and school age, 38,39 may be associated with the suboptimal development in early reading and math skills we identified, similar to that which has been observed in children born full term. 40,41 The lack of developmental differences in children born late preterm observed at 24 months and the reemergence of suboptimal development at preschool may also be related to limitations in the instruments used at the 24-month timepoint and to subtle differences in brain development that become apparent with advancing age.…”
Section: Figurementioning
confidence: 57%
“…[64][65][66] Rapid white matter development occurs over the late gestation period, with most fetal brain development occurring after 36 weeks of gestation. [64][65][66] Rapid white matter development occurs over the late gestation period, with most fetal brain development occurring after 36 weeks of gestation.…”
Section: Reductioninlatepretermbirthmentioning
confidence: 99%
“…The brain size of moderate and late preterm infants was smaller than that of term infants. [64][65][66] Rapid white matter development occurs over the late gestation period, with most fetal brain development occurring after 36 weeks of gestation. [67][68][69][70] Because of this physical development of the fetal brain, there are various risks in late preterm babies compared with in term babies, such as cerebral palsy, attention deficit hyperactivity disorder, mental retardation, and learning disabilities.…”
Section: Reductioninlatepretermbirthmentioning
confidence: 99%